PROBLEMS OF INTEGRATION AT THE FORMER SOVIET UNION - Еlena А. Hudorenko; Elena А. Nazarova; Konstantin A. Cherevyk (Статистика и экономика, 2016)
The article provides analysis of historical retrospective of integrationprocesses in former Soviet Union, ways and opportunities for furtherdevelopment thereof.The authors make a study of the problems of development and functioningof Eurasian cooperation, the effectiveness of interaction with certain states,analyze the reasons of failures, emphasize the achievements results ofcooperation, point out the opportunities for integration processes betweendifferent CIS and provide practical recommendations for effectiveness thereof in former Soviet Union.